Which practices co‐deliver food security, climate change mitigation and adaptation, and combat land‐degradation and desertification? - Smith, Pete; Calvin, Katherine; Nkem, Johnson; Campbell, Donovan; Cherubini, Francesco; Grassi, Giacomo; Korotkov, Vladimir; Hoang, Anh Le; Lwasa, Shuaib; McElwee, Pamela; Nkonya, Ephraim M.; Saigusa, Nobuko; et al. (Wiley, 2020)
There is a clear need for transformative change in the land management and food production sectors to address the global land challenges of climate change mitigation, climate change adaptation, combatting land‐degradation and desertification, and delivering food security (referred to hereafter as “land challenges”). We assess the potential for 40 practices to address these land challenges and find that: